The intensity of competition in manufacturing and service sectors: The determinant factors in ASEAN countries' context - Abdullah, Haim Hilman; Warokka, Ari; Md Dahlan, Nuarrual Hilal (2010)
The search of determinant factors of the intensity of competition is a long quest for developing countries since the 1960s, as the main part to determine their development policies.Intensity of rivalry in an industry affects the competitive environment and influences the ability of existing firms to achieve profitability.High intensity of rivalry means competitors are aggressively targeting each other's markets and aggressively pricing products.This represents potential costs to all competitors within the industry. Several factors determine the intensity of competitive rivalry in an industry, therefore, it is a must for any company to understand what factors have more weight in the industry the company operates.This paper aims to describe the determinant factors of the intensity of competition and its implications o manufacturing and service based companies among ASEAN countries.Actions taken by companies in these two sectors provide new insights into what manufacturing and service based companies might expect to occur and how they could respond to such threat.By using the data panel of six ASEAN countries for four years (2006-2009) observation, this paper finds that technological change, globalization, and increased competition are the most important environmental challenges facing manufacturing and service sectors today.Technology, in particular, seems to be acting as one of the principal accelerator toward hypercompetitive rivalry in manufacturing and service sectors.